ANALYSIS OF ENTREPRENEURIAL CHARACTERISTICS AND ENTREPRENEURIAL SKILLS ON BUSINESS SUCCESS IN CULINARY MSMEs in SUKABUMI CITY - Nurul Agustine; R Deni Muhammad Danial; Dicky Jhoansyah (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
This study was motivated by the rapid growth of culinary businesses in Sukabumi City. However, there are problems due to inadequate levels of entrepreneurial characteristics and entrepreneurial skills that hinder the success of culinary businesses in Sukabumi City. This study aims to examine and analyze the effect of entrepreneurial characteristics and entrepreneurial skills on the success of micro, small and medium enterprises (MSMEs) in the culinary sector in Sukabumi City. The research method used is descriptive qualitative research. Primary data were collected through observation and interviews, while secondary data were collected through literature study. The results of this study indicate that entrepreneurial characteristics and entrepreneurial skills simultaneously influence business success, thus emphasizing the importance of developing both aspects to improve competitiveness and business sustainability in the culinary sector.